Mortality in kittens is associated with a shift in ileum mucosa-associated enteroccoci from E. hirae to biofilm-forming E. faecalis and adherent E. coli - Ghosh, Anuradha; Borst, Luke; Stauffer, Stephen H.; Suyemoto, Mitsu; Moisan, Peter; Zurek, Ludek; Gookin, Jody L. (My University, 2013)
Approximately ~15% of foster kittens die before 8-wks of age with most of these kittens demonstrating clinical signs or post-mortem evidence of enteritis. While a specific cause of enteritis is not determined in most cases; these kittens are often empirically administered probiotics that contain enterococci. The enterococci are members of the commensal intestinal microbiota but can also function as opportunistic pathogens. Given the complicated role of enterococci in health and disease, it would be valuable to better understand what constitutes a “healthy” enterococcal community in these kittens and how this microbiota is impacted by severe illness. In this study, we characterize the ileum mucosa-associated enterococcal community of 50 apparently healthy and 50 terminally ill foster kittens. In healthy kittens, E. hirae was the most common species of ileum mucosa-associated enterococci and was often observed to adhere extensively to the small intestinal epithelium. These E. hirae isolates generally lacked virulence traits. In contrast, non-E. hirae enterococci, notably E. faecalis, were more commonly isolated from the ileum mucosa of kittens with terminal illness. Isolates of E. faecalis had numerous virulence traits and multiple antimicrobial resistance. Moreover, attachment of E. coli to the intestinal epithelium was significantly associated with terminal illness and was not observed in any kitten with adherent E. hirae. These findings identify a significant difference in species of enterococci cultured from the ileum mucosa of kittens with terminal illness compared to healthy kittens. In contrast to prior case studies that associate enteroadherent E. hirae with diarrhea in young animals, these controlled studies identified E. hirae as more often isolated from healthy kittens and adherence of E. hirae as more common and extensive in healthy compared to sick kittens.
Keywords: Kittens; Enteroccoci; Enterococcus hirae; Enterococcus faecalis; Escherichia coli; Enteritis; Intestinal microbiota